Penerimaan Konsumen Muslim Terhadap Produk Luar Negeri di UIN K.H. Abdurrahman Wahid Pekalongan (Studi Pada Eskrim MIXUE) - Abdillah Dwi Prasetyo; Alfiati Ruba’atin; Grecia Adis Vanessa; Isnaenatul Azizah; Kholilah Kholilah; Vita Tri Indriani (Global Leadership Organizational Research in Management, 2023)
This research aims to explore the level of acceptance among Muslim consumers towards foreign products, with a focus on Eskrim Mixue in the environment of students at UIN K.H. Abdurrahman Wahid Pekalongan. The research method used is qualitative research with a descriptive approach. Primary data was obtained through interviews with students who have consumed Eskrim Mixue, while secondary data consists of literature related to Islamic marketing, consumption in Islam, and factors influencing purchase interest. The research findings indicate that factors influencing consumer purchase interest in Eskrim Mixue include affordability, attractive packaging, product branding on social media, product quality, as well as product cleanliness and hygiene. Consumers also pay special attention to the halal label on products as a sign of both halal status and good quality. Islamic marketing is considered crucial in supporting the purchase interest of Muslim consumers. This research provides insights into how Muslim consumers at UIN K.H. Abdurrahman Wahid Pekalongan accept foreign products, particularly Eskrim Mixue, while considering aspects of Islamic marketing and adherence to Islamic principles in consumption. This study is expected to assist manufacturers in designing marketing strategies that align with Islamic values and create products that are better accepted by Muslim consumers..